Experimental study on the influencing factors of hydraulic fracture initiation from prefabricated crack tips. (1st June 2021) - Liu, Zhenghe; Yang, Jun; Yang, Lusheng; Ren, Xiaokai; Peng, Xuan; Lian, Haojie
Highlights: Hydraulic fracturing experiments with longitudinal(axial) pre-cracks on boreholes were conducted. The conditions under which hydraulic fractures can initiate from pre-crack tips were studied. The influence of the inclination angles of pre-cracks on crack initiation location was investigated. The effects of confining stresses, fracturing fluid viscosities, and leak-off were considered. Abstract: In this work, large-scale true triaxial tests were conducted with sandstone specimens to investigate several factors that determine whether hydraulic fractures can propagate from the tips of axial prefabricated cracks (pre-cracks). Specifically, we investigated the influence of pre-crack inclination angles on hydraulic fracture initiation locations and how the critical pre-crack angle varies with different confining stresses, fluid viscosities, and leak-off effects. The experimental results show that (1) the critical pre-crack angle declines with an increase in the horizontal stress difference. When the viscosity of the fracturing fluid is maintained at 70 mPa·s, as the horizontal stress difference increases from 2 MPa to 3 MPa to 4 MPa, the critical pre-crack angle decreases from 90° to 75° to 70°. (2) The critical pre-crack angle increases with an increase in the fracturing fluid viscosity. With a 3 MPa horizontal stress difference, the critical pre-crack angle increases from 60° to 70° to 75° as the viscosity of the fracturing fluid increases from 1 mPa·s to 40 mPa·s to 70 mPa·s. Under the condition that the horizontal stress difference is set to 4 MPa, as the fracturing fluid viscosity increases from 1 mPa·s to 40 mPa·s to 70 mPa·s, the critical pre-crack angle increases from 50° to 65° to 70°. (3) After waterproof treatment of the boreholes and pre-cracks, the critical pre-crack angle increases from 75° to 80° to 85° as the viscosity of the fracturing fluid increases from 1 mPa·s to 40 mPa·s to 70 mPa·s under the condition that the horizontal stress difference is fixed at 4 MPa.